PERAN PROJECT MANAGER DAN FINANCE MANAGER DALAM PELAKSANAAN STRATEGI BRAND COMMUNICATION UNTUK MENINGKATKAN BRAND AWARENESS DAN BRAND ENGAGEMENT MAMI AYAM POP MELALUI KAMPANYE “FLAVOR AND TUNES POP” - Kartika Dewi Hadiyono Loekito; Muhammad Bayu Widagdo (Interaksi Online, 2026)
The increasing competition in the culinary industry encourages Micro, Small, and Medium Enterprises (MSMEs) to implement effective communication strategies to improve brand awareness and brand engagement. Mami Ayam Pop, a culinary MSME in Semarang, experienced low brand recognition, as indicated by 76.7% of respondents who were unfamiliar with the brand and 81.2% who did not recognize its positioning as a specialty Ayam Pop restaurant. This study aimed to increase Mami Ayam Pop's brand awareness from 23.3% to 68.5% and enhance brand engagement through the Flavor and Tunes Pop campaign, which integrated Instagram and TikTok social media, collaborations with micro-influencers, and brand activation programs, including Vote Your Iftar Flavor, Ramadhan Satnight Tunes, and POP Bite Reaction. During the campaign, the Project Manager was responsible for campaign planning, coordination, and evaluation, while the Finance Manager managed budgeting, financial administration, and sales performance evaluation. This study employed the AISAS (Attention, Interest, Search, Action, Share) model using a descriptive quantitative approach. Data were collected through pre-test and post-test surveys involving 202 respondents, observations, documentation, and social media performance analysis. The findings indicate improvements in brand awareness, social media reach and engagement, consumer participation, and sales performance. These results demonstrate that the Flavor and Tunes Pop campaign effectively enhanced brand visibility, strengthened Mami Ayam Pop's positioning as a specialty Ayam Pop restaurant, and increased consumer engagement.